Financial Performance Analysis in Perspective of Capital, Asset, Management, Earning, and Liquidity (CAMEL) Methods - Hasan, Maskur; D’Ornay, Anastasia; Rara, Tasik (Amsir Management Journal, 2020)
This research aims to find out Is the financial performance of PT. Bank Sulselbar 2015-2018, which reviewed from the perspective of the Capital, Asset, Management, Earning, and Liquidity or commonly abbreviated as “CAMEL” method has it received the predicate of being healthy or not? The data collected is the company’s financial statement data obtained from Bank Sulselbar with a research period from 2015 to 2018. With the existence of standard measurement of bank health level, PT. Bank Sulselbar can be known the amount of the performance scale all this time. Besides, it can also be seen what factors influence the high/low weight values held for the assessment of bank health level with the perspective of the CAMEL analysis method.